(1226) The role of the rate of exchange in the management of the socialist economy دور سعر الصرف في إدارة الاقتصاد الاشتراكي - Kulczycki, Marek (The Institute Of National Planning., 2018)
The aim of this paper is to prove that the economic authorities which manage the socialist economy must take into consideration the level of all the parameter / searing Norma / including the rate of exchange, as well as regulate its level according to changes occurring in the economic situation of a given country and abroad.